Self-harm presentation across healthcare settings by sex in young people - Marchant, Amanda; Turner, Samantha; Balbuena, Lloyd; Peters, Evyn; Williams, Dave; Lloyd, Keith; Lyons, Ronan; John, Ann (International Journal of Population Data Science, 2019)
Background Accurate data on self-harm is crucial to suicide prevention efforts. It has been previously found that around twice as many people who self-harm seek help in primary care than in secondary care. Little is known about how contacts for self-harm differ across settings at a population level. This study utilised individual-level linked data across GP, Emergency Departments (ED), outpatients and hospital admissions examining contacts across settings and time by sex for self-harm in 10-24 year olds. Methods A whole-population based e-cohort study of routinely collected healthcare data was conducted. Rates of self-harm across settings over time by sex were examined. Individuals were categorised based on the service(s) to which they presented. Results A total of 937,697 individuals aged 10-24 years contributed 5,369,794 person years of data from the 01.01.2003-30.09.2015. There were differences in self-harm contacts by demographic variables particularly with regards to sex and admissions to hospital following ED attendance. Conclusion This is the first study to compare self-harm in people aged 10-24 years across primary care, EDs, and hospital settings in the UK. The high rates of self-harm in primary care and for young men in EDs highlight these as important settings for intervention. Understanding patterns of presentation will inform service planning and configuration for follow-up care and could inform tailored support, for example for males in ED. Linked data provides important evidence to support the development of interventions across healthcare settings.